The evolving mechanical response of curly hair fibres subject to fatigue testing - Ngoepe, Malebogo N.; Cloete, Elsabe; van den Berg, Claire; Khumalo, Nonhlanhla P. (Journal of the mechanical behavior of biomedical materials, 2021)
Cyclic testing of human hair reveals important details about the behaviour of fibres over many cycles of loading. Phenomena which are observed under static tensile tests give important clues about the form and behaviour of hair fibres, but these do not necessarily remain constant on the inevitable march to failure. In previous work, we demonstrated that curly fibres exhibited a toe-region during tensile tests. The form of curly fibres could be altered by mechanical manipulation but the curl could be recovered upon immersion in water. In this study, where straight and curly fibres are subject to cyclic loading, this characteristic toe-region was shown to be present in the first cycle of loading (for curly fibres). As the number of cycles increased (and the curly fibres progressively became straighter), the stress-strain response of curly fibres started to resemble that of straight fibres. This observation supports our previous hypothesis, which states that the toe-region can be attributed to the presence of a hydrogen bonding mechanism, which is present in curly fibres only, and can be altered by mechanical force. Interestingly, the alteration in load-bearing pattern in curly fibres did not necessarily translate to increased endurance, demonstrating that the relationship between fatigue and strength is a complex one in hair fibres.